2006
DOI: 10.1038/sj.cr.7310103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of non-adherent suspended neutrophils to complement opsonized pathogens: a new assay using optical traps

Abstract: Phagocytosis of opsonized pathogens by circulating non-adherent neutrophils is an essential step in host defense, which when overwhelmed contributes to sepsis. To investigate the role played by ligation of complement receptors CR3 and CR4 in non-adherent neutrophils, we designed a novel assay system utilizing dual optical traps, respectively, holding a suspended unactivated cell and presenting a specific ligand-coated bead to the cell surface. We chose anti-CD18 as an example ligand, mimicking the bacterial op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Instead, careful inspection of individual live cells (Figs 1, 2) is required to reveal subtle nuances that otherwise would be obscured by cell-to-cell baseline variability and to quantify the causal sequences and detailed timelines of immunophysical events that control these functions. Modern experimental techniques designed to characterize single cells with continually improving resolution include confocal microscopy, atomic force microscopy, optical tweezers, micro-and nano-fabrication and automated micropipette manipulation (Dewitt and Hallett, 2002;Zhelev et al, 2004;Suzuki et al, 2006;Jaumouille and Grinstein, 2010;Lomakina and Waugh, 2010;Lee et al, 2011). In addition, growing computational power is advancing all areas of physical immunology (Herant et al, 2006;Zhang and Morikis, 2006;Onsum and Rao, 2009;Herant et al, 2011;Liu et al, 2011).…”
Section: Single-cell Immunophysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, careful inspection of individual live cells (Figs 1, 2) is required to reveal subtle nuances that otherwise would be obscured by cell-to-cell baseline variability and to quantify the causal sequences and detailed timelines of immunophysical events that control these functions. Modern experimental techniques designed to characterize single cells with continually improving resolution include confocal microscopy, atomic force microscopy, optical tweezers, micro-and nano-fabrication and automated micropipette manipulation (Dewitt and Hallett, 2002;Zhelev et al, 2004;Suzuki et al, 2006;Jaumouille and Grinstein, 2010;Lomakina and Waugh, 2010;Lee et al, 2011). In addition, growing computational power is advancing all areas of physical immunology (Herant et al, 2006;Zhang and Morikis, 2006;Onsum and Rao, 2009;Herant et al, 2011;Liu et al, 2011).…”
Section: Single-cell Immunophysicsmentioning
confidence: 99%
“…For example, pipette manipulation of the target particle overcomes the difficulty "of presenting the stimulus to the cell at a defined time and at a defined location" (Dewitt and Hallett, 2002). The addition of a second micropipette, which can be used to partially aspirate the cell itself and lift it above the chamber bottom, enables the study of chemotaxis and phagocytosis without interference from intracellular processes that would otherwise coordinate adhesion to a substrate [alternatively, a laseroptical trap can be used at a low laser power to suspend phagocytes above the chamber bottom (Suzuki et al, 2006)]. Following stimulation, initially quiescent, pipette-held cells exhibit pronounced phagocytic (Fig.…”
Section: Pure Chemotactic Compared With Pure Phagocytic Response By Nmentioning
confidence: 99%
“…Thus "sinking phagocytosis", if it were possible, may be the energetically easier option. Thus, this early laser trap study [3] has already suggested that, in neutrophils at least, pseudopodia extension is the preferred route. It will be interesting to see whether this approach can be used with macrophages (or other phagocytic cells) and whether the "sinking" type of phagocytosis can be provoked by this method of stimulus presentation.…”
mentioning
confidence: 94%
“…Both may constitute other signals to the cell. In an elegant report by Suzuki et al in this issue of Cell Research [3], these problems are overcome by using laser optical traps to hold the particle and the cell. The laser trap exerts a holding force on the cell and the particle which can hold the cell in suspension.…”
mentioning
confidence: 99%
See 1 more Smart Citation